WORKFLOW COMPARISON IN SUBPERIOSTEAL IMPLANTOLOGY: TRADITIONAL VS. DIGITAL APPROACHES - Ioan Sarbu; Andreea Mihaela Custura; Vlad-Gabriel Vasilescu; Doriana Agop Forna; Vladimir Năstasie; Adelin Radu; Norina Consuela Forna; Kamel Earar (Romanian Journal of Oral Rehabilitation)
Aim of the study This study aims to conduct a comparative clinical and technological examination of standard analogue versus digital subperiosteal implants for treating patients with severe alveolar ridge atrophy. Materials and methods Two illustrative clinical workflows were analysed to demonstrate the practical and technological evolution of subperiosteal implantology. The first workflow involved the fabrication and placement of a cast cobalt-chromium implant using a traditional analogue method, which included direct intraoperative bone impression and a two-stage surgical protocol. The second workflow followed a fully digital approach, integrating CBCT-based virtual planning, CAD/CAM design, and fabricating a custom titanium framework via selective laser melting (SLM), executed in a single surgical stage. The comparison focused on surgical procedures, laboratory methodologies, and postoperative outcomes to highlight the key differences between the two approaches. Results Several surgical procedures and manual intraoperative adjustments were necessary for the analogue workflow to guarantee implant fit. The healing process was uneventful; however, the period of treatment was prolonged. The digital method allowed for quick prosthetic temporization, decreased surgical morbidity and allowed for the perfect preoperative design. The titanium framework exhibited superior anatomical conformity and patient comfort. The material properties and surface finish of the digitally fabricated implant were exceptional. Conclusions Digital subperiosteal implants signify a substantial advancement in the treatment of individuals with severe bone atrophy. In contrast to the conventional analogue method, the digital protocol provides enhanced accuracy, less morbidity, and faster prosthetic recovery. The clinical benefits of incorporating cutting-edge materials and new technology into contemporary oral implantology are highlighted by these advancements.